ANALISIS HUBUNGAN KAUSALITAS ANTARA VARIABEL KUALITAS PRODUK DAN PROMOSI DALAM PROSES PEMBENTUKAN KEPUTUSAN PEMBELIAN: Sebuah Studi Kasus tentang Pemasaran “Air Mineral Dalam Kemasan” di Kota Bekasi - Wachyudhi N (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
Every company is required to be ready to face the globalization competition. In this free business competition, the requirement for a company to succeed in the competition is to achieve the goal to create and retain customers. The purpose of this research is to analyze the effect of product quality and promotion on the purchasing decision of drinking water in packaging gallon of Aqua brand to the community in Bekasi City. Population in this research is a society that take decision in buying drinking water product in packing of Aqua gallon in the Bekasi Municipality. Data analysis method used is Quantitative Analysis Method by using questionnaires data which is distributed to the 100 respondent (as the sample). The results show that product quality and promotion variables have a significant influence on purchasing decisions.